Association between soft drinks consumption and asthma: a systematic review and meta-analysis - Abdulmohsen Hamdan Al-Zalabani; Ibrahim Noor Elahi; Abdullah Katib; Abdulmajeed G Alamri; Abdulrahman Halawani; Nasser M Alsindi; Mohammed Almatrafi; Anke Wesselius; Kelly F J Stewart (BMJ Open)
Objectives To carry out meta-analysis and systematic review on the association between soft drinks consumption and asthma prevalence among adults and children.Design Systematic review and meta-analysis of observational research.Data sources Medline, Scopus, ISI Web of Science and the Cochrane Library were searched up to December 2018.Eligibility criteria We included observational studies investigating the association between soft drinks consumption (including maternal consumption during pregnancy) and asthma or wheeze.Data extraction and synthesis Data were extracted by one author and reviewed independently by two other authors. The most adjusted estimate from each original study was used in the meta-analysis. Meta-analysis was conducted using random-effects model. The quality of studies was assessed using the Newcastle–Ottawa scale and heterogeneity was evaluated using I2 statistic.Results Of 725 publications originally identified, 19 were included in this systematic review, including 3 cohort studies and 16 cross-sectional studies. Ten articles reported on children up to 18 years, 5 articles on adults (>18 years) and 2 articles on prenatal exposure. In total, 468 836 participants were included, with more than 50 000 asthma cases. Soft drinks consumption was associated with significantly increased odds of asthma in both adults (OR=1.37; 95% CI, 1.23 to 1.52) and children (OR=1.14; 95% CI, 1.06 to 1.21). Prenatal exposure had marginally statistically significant association (OR=1.11; 95% CI, 1.00 to 1.23) with asthma in children. In subgroup analysis for childhood exposure, the association persists for sugar-sweetened soft drinks but not for carbonated drinks.Conclusion Our findings show a positive association between soft drinks consumption and asthma prevalence, mostly from cross-sectional studies. Therefore, more longitudinal research is required to establish causality.